- #1

- 11

- 0

Hello, I'm struggling with a simple problem here.

It asks me to solve the following initial value problem:

So far I've calculated the integration factor μ(x) = e

http://www4c.wolframalpha.com/Calculate/MSP/MSP36171f59839bdf0g6cbd000044defig6e40h0ei0?MSPStoreType=image/gif&s=64&w=256.&h=47. [Broken]

The problem I'm having is that the equation I got is different than the equation in the first line of the solution:

I don't understand how the e

It asks me to solve the following initial value problem:

So far I've calculated the integration factor μ(x) = e

^{x-x2}and I multiplied both sides of the equation by it and got this:

http://www4c.wolframalpha.com/Calculate/MSP/MSP36171f59839bdf0g6cbd000044defig6e40h0ei0?MSPStoreType=image/gif&s=64&w=256.&h=47. [Broken]

The problem I'm having is that the equation I got is different than the equation in the first line of the solution:

I don't understand how the e

^{x-x2}⋅(1 - 2x)⋅y disappeared

**EDIT:**Actually, nevermind. My brain was too lazy to realize that the left part of the equation is equal to the derivative of e

^{x-x2}⋅y so I could just simplify it

Last edited by a moderator: